Effect of antiplatelet and/or anticoagulation medication on the risk of tympanic barotrauma in hyperbaric oxygen treatment patients, and development of a predictive model - Howard, A.E.; Buzzacott, Peter; Gawthrope, I.C.; Banham, N.D. (2020)
Copyright: This article is the copyright of the authors who grant Diving and Hyperbaric Medicine a non-exclusive licence to publish the article in electronic and other forms.